Role of viruses in Kenyan children presenting with acute encephalopathy in a malaria-endemic area. - Schubart, C; Mturi, N; Beld, MG; Wertheim, P; Newton, C (2006)
In malaria-endemic areas, it is difficult to differentiate between cerebral malaria (CM), bacterial meningitis, and viral encephalitis. We examined the cerebrospinal fluid of 49 children who fulfilled the World Health Organization's (WHO) definition of CM and in 47 encephalopathic children, without malaria, looking for viruses with polymerase chain reaction. In the children with CM, four (9%) had evidence of Herpes simplex virus 1 in the cerebrospinal fluid, whereas in the encephalopathy group without malaria, six (12%) were positive. A significant proportion of children who fulfil the WHO clinical definition of CM may have viral encephalitis.